Evolution of Chemosensitivity and Resistance Assays as Predictors of Clinical Outcomes in Epithelial Ovarian Cancer Patients - J. Monk, Bradley; J. Herzog, Thomas; S. Tewari, Krishnansu (Current Pharmaceutical Design, 2016)
Epithelial ovarian cancer (EOC) is responsible for more cancer-related deaths than any other malignancy of the female reproductive system. The standard of care for advanced EOC involves a combination of cytoreductive surgery and platinum-based chemotherapy. Although a majority of patients respond to a platinum-containing regimen, many fail to respond to first-line treatment (platinum-refractory disease) or experience disease progression within 6 months of completing treatment (platinum-resistant disease). Even in patients who initially respond to platinum-based therapy, secondary development of platinum resistance is common. Many chemotherapeutic regimens with comparable efficacy and toxicities are available, leaving the determination of optimal therapy to the physician’s discretion. There have been many efforts over the years to develop accurate predictors of outcomes in patients treated with chemotherapy to help inform treatment decisions. Predictive treatment markers are particularly relevant in a disease such as EOC, where a large number of similarly efficacious chemotherapy regimens are available. Chemosensitivity and resistance assays (CSRAs) are attractive approaches to interrogate the efficacy and complex biology of EOC. Some early predictive cellular tests, such as the early clonogenic assays, were limited by technical and logistical issues. Over time, changes in these assays have improved their prognostic and predictive value, but there is still a lack of widespread adoption due to methodological difficulties or limited clinical validation. Herein, we provide an overview of the evolution of CSRAs used to predict outcomes in patients treated with chemotherapy that have been evaluated for use in EOC, with a focus on the latest generation chemoresponse assay.
Keywords: chemotherapy